2007
DOI: 10.1016/j.bpc.2007.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical studies of the interaction of the lipoheptapeptide surfactin with lipid bilayers of l-α-dimyristoyl phosphatidylcholine

Abstract: ochemical studies of the interaction of the lipoheptapeptide surfactin with lipid bilayers of L-α-dimyristoyl phosphatidylcholine. Biophysical Chemistry, Elsevier, 2007, 128 (2-3) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…It can thus interfere with biological membrane integrity in a dose-dependent manner. The effect of surfactin on artificial membrane was studied in detail on different models using atomic force microscopy (Deleu et al 1999a(Deleu et al , 2001Francius et al 2008), light scattering, differential scanning calorimetry, small-angle neutron scattering and cryo-electron microscopy (Kell et al 2007). Studies on lipid vesicles suggest that at low concentration (surfactin-to-lipid mole ratio R b lower than 0.04 in the membrane), surfactins insert exclusively in the outer leaflet of the membrane inducing only limited perturbation.…”
mentioning
confidence: 99%
“…It can thus interfere with biological membrane integrity in a dose-dependent manner. The effect of surfactin on artificial membrane was studied in detail on different models using atomic force microscopy (Deleu et al 1999a(Deleu et al , 2001Francius et al 2008), light scattering, differential scanning calorimetry, small-angle neutron scattering and cryo-electron microscopy (Kell et al 2007). Studies on lipid vesicles suggest that at low concentration (surfactin-to-lipid mole ratio R b lower than 0.04 in the membrane), surfactins insert exclusively in the outer leaflet of the membrane inducing only limited perturbation.…”
mentioning
confidence: 99%
“…pores in the membrane, and the lipid bilayer is progressively disrupted into sheet-like lamellar membrane fragments due to increasing strains in the membrane caused by further uptake of surfactin molecules (up to 10 mol%). Finally, at a surfactin concentration higher than 10 mol%, thread-like micelles of 6.5 nm in diameter were detected which tended to organize into loops of various sizes (Kell et al, 2007;Boettcher et al, 2010;Liu et al, 2010;Shen et al, 2010a). Surfactin-membrane interactions can also be described via the quantification of the local surfactin-to-lipid mole ratio within the membrane R b .…”
Section: Impact Of Surfactin Naturementioning
confidence: 99%
“…Membrane lyses or solubilisation to micelles begin at R b ~ 0.22 and a concentration of 9 μmol/l (Heerklotz and Seelig, 2007). Periodic variations of fluid, surfactin-rich regions and gel lipid-rich domains within the bilayer membrane result in the formation of stable nanoripple structures with intriguing potential in biomedical and biotechnological applications Kell et al, 2007;Banat et al, 2010). Membrane penetration by surfactin is facilitated by the presence of cations (Maget-Dana & Ptak, 1995).…”
Section: Impact Of Surfactin Naturementioning
confidence: 99%
“…Due to their specific amphiphilic structure surfactins show unique surface-, interface-and membrane-active properties by integrating into lipid vesicles [19,20] or monolayers [21][22][23][24][25] and they possess a high tendency for self-aggregation by forming micelles [26][27][28][29]. Previous studies on the effects of surfactin on mycoplasma and membrane coated viruses [16,17] revealed a pure physicochemical mechanism which leads to the disintegration of the envelop lipid membranes.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate its mechanism of action on the molecular level and to design efficient procedures for biotechnological usage biomimetic studies of surfactin interaction with model membranes are needed. With this aim we recently initiated systematic examinations of surfactin's lytic action on unilamellar DMPC vesicles using physicochemical techniques such as differential scanning calorimetry (DSC), static light scattering (SLS), small angle neutron scattering (SANS) and cryo-electron microscopy (cryo-TEM) [20].…”
Section: Introductionmentioning
confidence: 99%